Dynamic evidence for metal ion catalysis in the reaction mediated by a flap endonuclease - Tock, Mark R. (Oxford University Press, 2003)
On the basis of structural work, metal ions are proposed to play a catalytic role in reactions mediated by many phosphoryl transfer enzymes. To gain dynamic support for such mechanisms, the role of metal ion cofactors in phosphate diester hydrolysis catalysed by a flap endonuclease has been studied. The pH maximal rate profiles were measured in the presence of various metal ion cofactors; in each case, a single ionic form of the enzyme/cofactor accounts for the pH dependence. The kinetic pK(a)s display good correlation with the acidity of the corresponding hexahydrated metal ions, which strongly suggests a role for metal-bound hydroxide, or its equivalent ionic species, in the reaction. Comparing rates of reaction in the pH-independent regions, a small negative β(nuc) value is observed. This suggests that expected trends in the nucleophilicity of the various metal-bound hydroxides are balanced by a second form of metal ion catalysis that is related to the acidity of the hexahydrated metal ion. This is likely to be either electrophilic catalysis or leaving group activation.